2019
DOI: 10.1002/ajb2.1213
|View full text |Cite
|
Sign up to set email alerts
|

What makes a weed a weed? A large‐scale evaluation of arable weeds through a functional lens

Abstract: Premise of the Study Despite long‐term research efforts, a comprehensive perspective on the ecological and functional properties determining plant weediness is still lacking. We investigated here key functional attributes of arable weeds compared to non‐weed plants, at large spatial scale. Methods We used an intensive survey of plant communities in cultivated and non‐cultivated habitats to define a pool of plants occurring in arable fields (weeds) and one of plants occurring only in open non‐arable habitats (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 56 publications
4
52
1
Order By: Relevance
“…These traits can be divided in two categories. The first category of frequent and abundant weeds in maize shares rapid resources acquisition capacities through high SLA and high Ellenberg-N values. This is consistent with a recent study that showed that weeds were distinguished from other herbaceous species in open habitats by high values of SLA and Ellenberg-N, and that among crop weeds, those most specific to the cultivated environment also had high values of these indices [28]. The second category of frequent and/or abundant weeds have a strong colonization capacity with a low seed weight combined with a high fecundity.…”
Section: Weediness Traitssupporting
confidence: 92%
“…These traits can be divided in two categories. The first category of frequent and abundant weeds in maize shares rapid resources acquisition capacities through high SLA and high Ellenberg-N values. This is consistent with a recent study that showed that weeds were distinguished from other herbaceous species in open habitats by high values of SLA and Ellenberg-N, and that among crop weeds, those most specific to the cultivated environment also had high values of these indices [28]. The second category of frequent and/or abundant weeds have a strong colonization capacity with a low seed weight combined with a high fecundity.…”
Section: Weediness Traitssupporting
confidence: 92%
“…The first category of frequent and abundant weeds in maize shares rapid resources acquisition capacities through high SLA and high Ellenberg-N values. This is consistent with a recent study that showed that weeds were distinguished from other herbaceous species in open habitats by high values of SLA and Ellenberg-N, and that among crop weeds, those most specific to the cultivated environment also had high values of these indices [25]. The second category of frequent and/or abundant weeds have a strong colonization capacity with a low seed weight combined with a high fecundity.…”
Section: Weediness Traitssupporting
confidence: 92%
“…This study indicated that except three geophytes (Cyperus esculentus, Ledebouria sudanica and Stylochaeton hypogaeus) the flora is largely dominated by therophytes, which includes 95% of the recorded species. According to Bourgeois et al (2019), therophytes were the mostly weeds because of some adaptability among them higher specific leaf area, earlier and longer flowering, sunny and dry environments. Higher number of small sedge (Cyperus amabilis, Cyperus esculentus, Fimbristylis hispidula, Mariscus squarrosus and Kyllinga squamulata) found in this study is a characteristic of degraded land and showed the effect of rotation with others rainy crop mainly Groundnut and Maize.…”
Section: Structure Of the Floramentioning
confidence: 99%